Structural equation model to assess the impact of learning organization and commitment on the performance of research organizations - Khunsoonthornkit, Ardharn; Panjakajornsak, Vinai (My University, 2018)
This study analyzed the impact of learning organization and commitment on the performance of research and development organizations in Thailand. The research used a structural equation model based on an extensive review of relevant literature. The population and samples were drawn from full-time researchers in two science and technology organizations under the Thai Ministry of Science and Technology. A questionnaire survey was used to collect empirical data. The model fit was analyzed using the confirmatory factor analysis technique. The results showed that learning organization had a direct effect on organizational commitment and performance. However, commitment had no direct effect on organizational performance. Based on these results; scientific, and technology and development policy and planning should consider applying learning organization in research organizations.
Keywords: learning organization; organizational commitment; organizational performance; research and development organizations